2006
DOI: 10.1111/j.1469-8986.2006.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

An event‐related potentials study of face identification and naming: The tip‐of‐the‐tongue state

Abstract: With the aim of identifying event-related potential (ERP) correlates of the tip-of-the-tongue (TOT) state, we employed a task involving identification and naming of the faces of famous people with three response categories: KNOW (correct naming), DON'T KNOW (name not known), and TOT. Before 450 ms, no differences are observed between TOT and KNOW conditions in ERPs related to face processing and recognition. The smaller mean amplitude in TOT than in KNOW responses over the 550-750-ms interval and the N-TOT dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
47
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 66 publications
13
47
4
Order By: Relevance
“…As a result, the ranking of LNW amplitudes can be attributed to the amount of processing resources released after closure of the stimulus epoch: complete closure and release of processing resources in DON'T KNOW, incomplete closure in KNOW, because a subset of processing resources are probably engaged in name retrieval and in verification of whether the name retrieved corresponds to the face presented, and nonclosure in TOT, due to the blockage situation. However, as the authors (Díaz et al, 2007) indicated, it was possible that these differences were also modulated by the brain activity associated with the preparation and execution of the motor responses required in the task. The analysis of MRCP may help to corroborate this hypothesis.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…As a result, the ranking of LNW amplitudes can be attributed to the amount of processing resources released after closure of the stimulus epoch: complete closure and release of processing resources in DON'T KNOW, incomplete closure in KNOW, because a subset of processing resources are probably engaged in name retrieval and in verification of whether the name retrieved corresponds to the face presented, and nonclosure in TOT, due to the blockage situation. However, as the authors (Díaz et al, 2007) indicated, it was possible that these differences were also modulated by the brain activity associated with the preparation and execution of the motor responses required in the task. The analysis of MRCP may help to corroborate this hypothesis.…”
Section: Introductionmentioning
confidence: 93%
“…From initial sample of 20 university students who participated in the study of Díaz et al (2007), valid MRCP averaged waveforms were obtained from 14 participants (6 men and 8 women; age range 19-24 years). All were right-handed, with normal or corrected vision, and were healthy, with no history of neurological or psychiatric disorders and had not received any medical treatment in the 4 weeks prior to the experiment.…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations